PENGARUH KOMPRES SEREH HANGAT TERHADAP PENURUNAN NYERI RHEUMATOID ARTHRITIS PADA LANJUT USIA DI WILAYAH KERJA PUSKESMAS BOLIYOHUTO - Fadli Syamsuddin; Abdul Wahab Pakaya; Tarsiyah Tarsiyah (Zaitun (Jurnal Ilmu Kesehatan), 2020)
Rheumatoid Arthritis (RA) is a chronic autoimmune inflammation disorder or an autoimmune response where a person's immune system can be disrupted and dropped which causes the destruction of joint organs. One chronic or long-term joint disease is rheumatoid arthritis. This research aims to determine the effect of warm lemongrass compresses on reducing rheumatoid arthritis pain in the elderly. The design uses Quasy-experimental pretest and posttest involving the control and intervention groups. Respondents were 20 people. The experimental group was given warm lemongrass compresses once a day for 20 minutes. Whereas control group was not given intervention. The results of this study indicate a decrease in pain in the intervention group from the results of the paired T test obtained a value of P = 0.000 (α <0.05). It was concluded that there was a significant effect on the application of warm lemongrass compresses to reduce rheumatoid arthritis pain in the elderly. So this research is expected to help the community in dealing with rheumatoid arthritis pain using warm lemongrass compresses as traditional medicine.